Karakteristik Pendidikan Agama Islam pada Anak Tuna Grahita di SLB Bhakti Wiyati Giripeni Wates - Zahra, Tajkiatu; Rohman, Muhammad Fuad Al Azhar; Husna, Difa`ul (TSAQOFAH, 2024)
This research discusses the characteristics of PAI teachers in delivering material to mentally retarded children at SLB Bhakti Wiyati Giripeni, Wates. This research uses a phenomenological approach and qualitative research. There are three types of data collection techniques in this research, namely: Observation, Interview, and Documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, verification and drawing conclusions. The results of data analysis obtained from the research are the characteristics of PAI teachers in delivering material to mentally retarded children at SLB Bhakti Wiyati Giripeni Wates using different strategies both in terms of individuals, groups and a mixture of student characteristics.